The Influence Of Product Quality, Service Quality, And Promotion On Purchasing Decisions At PT. KOI Cafe Indonesia At Palembang Icon Mall - Ariani, Elsa Septi; Andriyani, Ima; Mayasari, Veny (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence of Product Quality, Service Quality, and Promotion on Purchasing Decisions at PT. KOI Cafe Indonesia. The sample in this study was 99 consumers of PT. KOI Cafe Indonesia. The analysis technique used was multiple linear regression analysis, processed using the computer program Statistical Product and Service Solution (SPSS) version 26. The results of the study indicate that Product Quality, Service Quality, and Promotion simultaneously influence Purchasing Decisions. This is proven through statistical testing, which indicates that the null hypothesis is rejected, thus accepting the alternative hypothesis. Partially, each of the independent variables—Product Quality, Service Quality, and Promotion—also proved to influence Purchasing Decisions. This conclusion is based on a significance value smaller than the predetermined probability limit, indicating that the influence is statistically acceptable.